ANALISIS PUISI “BAHASA LANGIT” KARYA ACEP ZAMZAM NOOR MELALUI PENDEKATAN ALIRAN NEW CRITICISM - Sophia, Ratna; Maulana, Muhammad Fanza; Dzikri, Rifqi Ahmad (Program Studi Tadris Bahasa Indonesia, 2025)
One form of manifestation of the results of human thought is literary works. Literary works are created, enjoyed, and appreciated by society, and the main purpose of their creation is to be enjoyable. One form of literary work is poetry. Poetry as one of the literary arts has a unique ability to inspire, stir emotions, and convey deep messages to readers or listeners through the use of unique and creative language. One of the poetry works that attracted attention in the Indonesian literary scene was